Evidence for male dispersal along the coasts but no migration in pelagic waters in dusky dolphins (Lagenorhynchus obscurus) - Cassens, Insa (2004)
Using nine nuclear species-specific microsatellite loci and two mitochondrial genefragments (cytochrome b and control region), we investigated the processes that have shapedthe geographical distribution of genetic diversity exhibited by contemporary dusky dolphin(Lagenorhynchus obscurus) populations. A total of 221 individuals from four locations (Peru,Argentina, Southwest Africa, and New Zealand) were assayed, covering most of the species’distribution range. Although our analyses identify a general demographic decline in thePeruvian dusky dolphin stock (recently affected by high natural and human-induced mortalitylevels), comparison between the different molecular markers hint at an ancient bottleneck thatpredates recent El Niño oscillations and human exploitation. Moreover, we find evidence of adifference in dispersal behavior of dusky dolphins along the South American coast and acrossthe Atlantic: while data in Peruvian and Argentinean waters are best explained by malespecificgene flow between these two populations, our analyses suggest that dusky dolphinsfrom Argentina and Southwest Africa recently separated from an ancestral Atlantic populationand, since then, diverged without considerable gene flow. The inclusion of a few NewZealand samples further confirms the low levels of genetic differentiation among most duskydolphin populations. Only the Peruvian dusky dolphin stock is highly differentiated,especially at mitochondrial loci, suggesting that major fluctuations in its population size haveled to an increased rate of genetic drift.